IMPLEMENTASI KEBIJAKAN PENGELOLAAN ARSIP DINAMIS DI PT. KONSTRINDO PUTRA PERKASA PALU PROVINSI SULAWESI TENGAH - Yunus, Yuniarti (Katalogis, 2019)
This research aims to find out the Implementation of Dynamic Archieve Management Policies at PT. Konstrindo Putra Perkasa in Palu City, Central Sulawesi. The usefulnes of this research is theoretical and practical. In the Literate review explains the concept of Public Policy and the Concept Archive Management Policy. The flow of thought by the theory of policy implementation Edward III which includes the factors of communication, disposition, resources and bureaucratic structure. Research white qualitative method, PT. Konstrindo Putra Perkasa Research Location in Palu City Central Sulawesi, Research time for the three month, Informants are elements of Leadership and staff. Definition Operational Concept related to the implementation model of the policy. Qualitative data type, and data sources namely Secondary data and Primary Data. The Discussion explained,explicity about the Implementation of Dynamic Archive Management Policy at PT. Konstrindo Putra Perkasa at PT. Konstrindo Putra Perkasa in Palu city, Central Sulawesi and concluded that the Dynamic Archive Management Policy at PT. Konstrindo Putra Perkasa In Palu Central Sulawesi not maximal was caused lack of human resources manager archives, facilities that have not been in accordance with aplicable standars and archival rules, and lack of socialization from the relevant goverment.